Potential probiotic yeasts isolated from the fish gut protect zebrafish (Danio rerio) from a Vibrio anguillarum challenge - Caruffo, Mario; Navarrete, Natalie; Salgado, Oscar; Díaz, Angélica; López, Paulina; García, Katherine; Feijóo, Carmen G.; Navarrete, Paola (Frontiers in Microbiology, 2015)
Due to the negative consequences associated with the use of antibiotics, researchers and food producers have studied alternatives, such as probiotics, for the control of fish diseases. The probiotic properties of yeasts in aquaculture have been scarcely considered. The present study investigated the probiotic properties of local yeast strains for aquaculture application in the protection of bacterial diseases. Yeast strains (n=15), previously isolated from the intestinal gut of healthy salmonids, yellowtail and croaker, were evaluated for their protection of zebrafish larvae following a Vibrio anguillarum challenge. We developed an infection model on zebrafish larvae with V. anguillarum, observing rapid mortality (≥50%) 5 days post immersion challenge. Infection of Tg(Lyz:DsRed)nz50 larvae with fluorescent-marked V. anguillarum showed the oro-intestinal as the natural route of infection concomitant with an inflammatory response of the larvae reflected by neutrophil migration outside the hematopoietic tissue. Thirteen of 15 strains increased the percentage of larvae survival after the V. anguillarum challenge, although no yeast showed in vitro anti-V. anguillarum activity. In a subset of yeasts, we explored yeast-larvae interactions using fluorescent yeast and evaluated larvae colonization by culture analysis. All fluorescent yeasts were located in the gastrointestinal tract until 5 days post inoculation (dpi). Yeasts reached 103 CFU/larvae at 0 dpi, although the persistence until 5 dpi of the viable yeast in the gut was different among the strains. These results reveal that some yeasts isolated from the gut of fish could be potential probiotics, reducing the mortality associated to V. anguillarum challenge, and suggest that gut colonization could be involved in the protective effect. Future studies should elucidate other mechanisms involved in yeast protection and verify the beneficial effects of probiotic use in commercial fish species.